Mediation in the Perspective of Islamic and Manmade Laws - Hafiz Khalid Rashid; Abdul Ghaffar (IUB) (Pakistan Journal of Islamic Research)
The research article: Mediation in the perspective Islamic and manmade laws is basically such type of research that contains the status and importance of mediation in perspective Islamic. Mediation and reconciliation in civil and criminal matters will be narrated briefly in this research article. . Matters relating social behavior are solved in the light of Qur’ān and Sunnah. Five kinds of Hoodoos are mentioned in Qur’ān extra-marital sexual intercourse (Zinā), False Parole of Extra-Marital Sexual Intercourse (Qaḏf), alcohol consumption (Šurb-al-kḫamr), theft (Sariqa) and street robbery (Hirāba or Qaṭ' al-tarīq) and are also analyzed. The Retributive Justice (Qiṣāṣ) and Compensation (Diyah) are the ones where the punishment is fixed by Allāh. Blasphemy laws are also introduced through sections 295-Band 295-C of the Pakistan Penal Code. According to Sec.295-c capital punishment is sanctioned for the accused after the approval of evidence. As human beings are social beings, disputes among them are inevitable. Judicial agreement of disputes is alas highly-priced, time eating and open for public. However Islamic regulations present for agreement of disputes by way of many methods of full inclusive of mediation. The motive of the paper is to take a look at ideas on mediation laid down in the Qur’ān and the Sunnah of Prophet Muḥammad (ﷺ) and the manmade laws. There is numerous training that may be found out from the exemplary conduct of the Prophet (ﷺ) who became a politically righteous individual with maximum moral and ethical values of the Prophet (ﷺ) to become civilized in settling their differences.